2018
DOI: 10.1016/j.bjpt.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Dual-task as a predictor of falls in older people with mild cognitive impairment and mild Alzheimer's disease: a prospective cohort study

Abstract: The dual-task predicts falls only in older people with mild cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 23 publications
2
47
0
Order By: Relevance
“…Our findings of an increased likelihood of falls in older adults with stroke or dementia are consistent with previous studies [6,[15][16][17]. There are a variety of factors that contribute to increased fall risk in the older adult population, including demographics (e.g., age, sex, race) [18,19], medical history (e.g., prior injuries, surgeries, pain, arthritis, diabetes, neurological disorders, cognitive dysfunction) [15,[19][20][21][22][23][24][25], increased health care needs (e.g., medical comorbidities, medications) [17,26], prior history of falls [18,[27][28][29][30], physical impairments [24,29], and environmental factors [30]. Older adults with neurological disorders may have increased fall risk in part because of their complex health care needs [6,16,17].…”
Section: Discussionsupporting
confidence: 84%
“…Our findings of an increased likelihood of falls in older adults with stroke or dementia are consistent with previous studies [6,[15][16][17]. There are a variety of factors that contribute to increased fall risk in the older adult population, including demographics (e.g., age, sex, race) [18,19], medical history (e.g., prior injuries, surgeries, pain, arthritis, diabetes, neurological disorders, cognitive dysfunction) [15,[19][20][21][22][23][24][25], increased health care needs (e.g., medical comorbidities, medications) [17,26], prior history of falls [18,[27][28][29][30], physical impairments [24,29], and environmental factors [30]. Older adults with neurological disorders may have increased fall risk in part because of their complex health care needs [6,16,17].…”
Section: Discussionsupporting
confidence: 84%
“…The difference between fallers and non-fallers in CoP area and medio-lateral CoP velocity during parallel stance was unchanged when a cognitive task was added, while the difference in CoP antero-posterior velocity increased (SMD from 0.26 to 0.37). Previous studies have shown that dual task-based tests are very useful in predicting falls in older people with cognitive impairment [95]. Similarly, the capability of the Timed-Up-and-Go test to classify fallers and non-fallers was also shown to increase with the addition of a cognitive task [96].…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, in order to infer information relative to specific neural areas and cognitive functions, protocols involving the so-called brain stress tests are employed [85]. These are the dual-task tests that are composed of walking while performing an additional motorcognitive task such as calling a phone number [86], talking or counting [87], or carrying a glass of water [88]. However, a considerable number of works in the related literature do not specify the testing protocol used to assess gait parameters, so it is difficult to compare and assess the results.…”
Section: Protocols For Gait Analysismentioning
confidence: 99%